Pendampingan Panitia Khusus II DPRD Kota Magelang dalam Pembahasan Raperda Kota Magelang tentang Pengarusutamaan Gender - Habib Muhsin Syafingi; Dyah Adriantini Sintha Dewi; Dilli Trisna Noviasari; Jihan Arsya Nabila (Universitas 17 Agustus 1945 Semarang, 2025)
This community service activity in the form of assistance aims to enhance the capacity of the Regional House of Representatives (DPRD) of Magelang City as a legislative body in formulating gender-responsive regulations through the drafting of the Regional Regulation on Gender Mainstreaming (Raperda PUG). This activity represents a commitment to supporting the development of regional regulations that are responsive to gender equality issues and provide legal certainty in achieving gender-inclusive national development, as mandated by Presidential Instruction Number 9 of 2000 on Gender Mainstreaming in National Development (Inpres No. 9/2000). To achieve broader gender equality—in family, community, national, and state life—it is necessary to implement gender mainstreaming strategies within national development, one of which is through the formulation of regional regulations. The assistance was carried out in two stages, namely preparation and implementation. The output of this activity consists of analyses and recommendations on the Raperda PUG, covering sociological and juridical aspects, which were presented both orally and in written form to the Special Committee II (Pansus II) of the DPRD of Magelang City.